Desconocimiento de las reglas ortográficas y su incidencia en el proceso de enseñanza-aprendizaje del área de la lengua escrita en los estudiantes del 9no año de educación general básica de la Unidad Educativa Caracol, cantón Babahoyo Provincia de Los Ríos - Bravo Medina, Yajaira Alejandrina (2019)
In our educational environment, without a doubt, one of the most complex tasks for children is to learn to write, but even more complex is to learn to write correctly. What does it mean to write correctly? The oral and written language are not constructed equal, in written language there are codes and forms that must be respected so that what we write has a coherence and a cohesion and therefore, is understood by the one who receives our message. One of those codes that we must take into account is the spelling Spelling, in short, helps the standardization of a language, something that is very important when there are different dialects in the same territory. It is worth mentioning that the rules of spelling are taught during the first years of primary education. These errors are increasingly common in the writing that students write schools, colleges and universities. The problems start from the school and the school, because the dictations and the newsrooms were forgotten. Spelling is the presentation of a person and that is why we should worry about improving it. People should be more interested in reading as this is a technique that helps us improve the spelling so that the recipient of our message captures it properly.